On a periodic type boundary-value problem for first order linear functional differential equations - Hakl, R.; Lomtatidze, A.; Šremr, J. (Нелінійні коливання, 2002)
Nonimprovable sufficient conditions are established for unique solvability of the boundary-value problem u`(t) = l(u)(t) + q(t), u(a) = λu(b) + c,
as well as for nonnegativeness of its solution, where l : C([a, b]; R) → L([a, b]; R) is a linear bounded
operator, q ∈ L([a, b]; R), λ ∈ R+, and c ∈ R. Знайдено достатнi умови, що не можуть бути полiпшенi, для однозначної розв’язностi граничної задачi u`(t) = l(u)(t) + q(t), u(a) = λu(b) + c, та невiд’ємностi її розв’язку, де l :
C([a, b]; R) → L([a, b]; R) — неперервний лiнiйний оператор, q ∈ L([a, b]; R), λ ∈ R+ та c ∈ R.